Catalytic Polarographic Analysis of Trace Amounts of Iron in Water Samples and Leafy Vegetables - Saraswathi, K.; Venkatasubba Naidu, N.; Padmaja, K. (Asian Journal of Chemistry, 2010)
A catalytic polarographic method for the determination of trace quantitiesof iron is developed using antipyrine as ligand in 0.05 M potassiumchloride medium. The procedure is extended for the analysis of water andagricultural samples for iron content.